THE EFFECT OF PRESSURE UPON HYDROGEN BONDING IN CHLORITE: A RAMAN SPECTROSCOPIC STUDY OF CLINOCHLORE TO 26.5 GPA - Kleppe A.K.; Jephcoat A.P.; Welch M.D. (My University, 2003)
The effect of pressure upon hydrogen bonding in synthetic end-member clinochlore, (Mg5Al)(Si3Al)O10(OH)8, has been studied in situ by high-pressure micro-Raman spectroscopy in a moissanite-anvil cell to 26.5 GPa at 300 K. The ambient spectrum consists of three OH-stretching bands between 3400 and 3650 cm 1 , attributed to the hydrogen-bonded interlayer OH, and a narrow band at 3679 cm 1 that is assigned to the non-hydrogen-bonded OH groups of the talc-like 2:1 layer. The pressure dependence of the OH modes is linear up to 6 GPa. Near 9 GPa a major discontinuity occurs in the pressure dependence of the interlayer OH-stretching modes. It involves frequency increases >100 cm -1 that indicate major changes in hydrogen bonding. The OH mode of the 2:1 layer does not show discontinuous behavior at 9 GPa. A further discontinuity occurs at ~16 GPa. This discontinuity affects both interlayer and 2:1 OH, and is likely to be associated with a change in the overall compression mechanism of clinochlore. The spectroscopic behavior is a completely reversible function of pressure. Predictions based upon recent high-pressure diffraction studies of hydrogen bonding and compression of clinochlore suggest that the 9 GPa transition is associated with attainment of an O 2-O 2-contact distance of 2.7 A.[PUBLICATION ABSTRACT]
Keywords: MINERALOGY; HYDROGEN; PRESSURE; SPECTRUM ANALYSIS; clinochlore